Using Multi-Channel Surface Analysis of Surface Waves and Resistivity Survey to Evaluate Road Damage - Suksawat, Taweephong; Ayawanna, Jiratchaya; Chaiyaput, Salisa (My University, 2026)
The study provides an analysis of road damage, which was Pathum Thani rural road no. 3012 (PT. 3012), in the Pathum Thani province, Thailand. A road was constructed along the irrigation canal with the construction of a retaining wall, while the roadway was supported with a foundation consisting of soil-cement columns. Longitudinal cracks and settlements appeared between the roadway and the road shoulder within five years after the completion of road construction. To evaluate and confirm the aforementioned problem, the soil investigation was utilized. Conventional geotechnical investigations often involve the utilization of in situ tests as the primary method, resulting in the collection of soil samples at specific locations, which do not cover a large area in the construction site. Therefore, this study aims to propose the combination of multi-channel analysis of surface waves (MASW) and resistivity survey techniques, which were employed to identify and evaluate the underlying cause of the observed damage by effectively identifying the subsurface layer throughout a large area under undisturbed conditions. The soil investigation results confirmed that the differential settlement occurred because the roadway was supported by soil-cement columns, while the road shoulder was not supported by soil-cement columns. Consequently, it was easy to recognize and confirm the problem with the imaging of the subsurface layers from the findings of those MASW and resistivity survey approaches.
Keywords: Geotechnics; MASW; Resistivity survey; Soft soils; Subsurface investigations